Antonini, Schon, Zemborain a lo largo y lo ancho del país - Waisman, Marina
Recorrido por las obras del estudio.
Keywords: ANTONINI, ANTONIO; ANTONINI, SCHON, ZEMBORAIN; SCHÖN, GERARDO; ZEMBORAIN, EDUARDO; HALL, MIGUEL; FERVENZA, JUAN CARLOS; ESTUDIOS DE ARQUITECTURA; TRAYECTORIA PROFESIONAL; CRITICA